2019
DOI: 10.1111/ecot.12224
|View full text |Cite
|
Sign up to set email alerts
|

Does good governance matter for FDI? New evidence from emerging countries using a static and dynamic panel gravity model approach

Abstract: This paper assesses the impact of institutional factors on foreign direct investment (FDI) attractiveness using a pool of 25 emerging host countries (ECs) for the period 1996–2012. In particular, the paper aims to examine whether higher institutional quality and good governance do improve FDI attractiveness, and thereby to identify which institutional factors are the main drivers of FDI in ECs. Using a static and dynamic panel gravity model with various estimation techniques, we find that FDI is positively and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 64 publications
5
19
0
2
Order By: Relevance
“…Thus, FDI inflows responsive to laws elevate international shareholding of FDI to local shareholding [72][73][74]. Studies have shown that collective good governance actions may enhance FDI inflows [75][76][77]. Thus, factors that improve investors' regulatory quality, including tax exemptions or reductions and flexible regulations, support the implementation of legal policies to safeguard the natural environment from uncontrolled exploitation of resources and pollution.…”
Section: The Connection Between Fdi and Co 2 Emissionsmentioning
confidence: 99%
“…Thus, FDI inflows responsive to laws elevate international shareholding of FDI to local shareholding [72][73][74]. Studies have shown that collective good governance actions may enhance FDI inflows [75][76][77]. Thus, factors that improve investors' regulatory quality, including tax exemptions or reductions and flexible regulations, support the implementation of legal policies to safeguard the natural environment from uncontrolled exploitation of resources and pollution.…”
Section: The Connection Between Fdi and Co 2 Emissionsmentioning
confidence: 99%
“…The size of a node represents the frequency of occurrence of a keyword. The top 10 high-frequency keywords are "infrastructure" (with citation counts of 66), "growth" (56), "governance" (43), "performance" (43), "institution" (40), "management" (36), "impact" (35), "determinant" (35), "developing country" (29), "foreign direct investment" (29) and "China" (29).…”
Section: Main Research Interests: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…Furthermore, other keywords such as "determinant", "impact", and "foreign direct investment" denote that the ways in which corruption affects foreign direct investment have been well explored. For example, research from the USA [32], the Middle East and North African countries [33] suggests that corruption, as an institutional factor, plays a significant role in determining investment activities, especially investment in infrastructure projects [34,35]. The frequency of the keyword "infrastructure" is the highest, which represents the research context of CICP.…”
Section: Main Research Interests: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…Furthermore, little is known about the impact of location attractiveness on the indicators for the establishment of a new business. Most research analyses the effects on the relocation of companies (Conroy et al, 2017;Kotler et al, 2019) or on foreign direct investment (Dunning, 2003;Younsi & Bechtini, 2019). Some studies analyse the interaction between location attractiveness and new business development at a regional level.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Location factors influence place selection, which may be more or less beneficial (Strzelczyk, 2015). Many studies have already highlighted the fact that countries that are attractive for business development (Godlewska-Majkowska & Komor, 2017;Strzelczyk, 2015) and for governance infrastructure (Younsi & Bechtini, 2019) are likely to attract more businesses and foreign direct investment. However, a policy of enhancing the business climate may be productive in some regions but not in others (Chin, 2020).…”
Section: Introductionmentioning
confidence: 99%